2018
DOI: 10.1371/journal.pone.0192380
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis arc5 and arc6 mutations differentially affect plastid morphology in pavement and guard cells in the leaf epidermis

Abstract: Chloroplasts, or photosynthetic plastids, multiply by binary fission, forming a homogeneous population in plant cells. In Arabidopsis thaliana, the division apparatus (or division ring) of mesophyll chloroplasts includes an inner envelope transmembrane protein ARC6, a cytoplasmic dynamin-related protein ARC5 (DRP5B), and members of the FtsZ1 and FtsZ2 families of proteins, which co-assemble in the stromal mid-plastid division ring (FtsZ ring). FtsZ ring placement is controlled by several proteins, including a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 72 publications
5
27
1
Order By: Relevance
“…We observed stomatal guard cell chloroplasts and counted the frequency of stromules in 1-and 2-day old cotyledons, taken as a developing leaf, and 5-day old cotyledons, as a developed leaf. Abnormal morphology of chloroplasts in stomata has not been reported in wild-type seedlings (Fujiwara et al 2018) and we observed normal morphology of the chloroplasts in stomata and pavement cells in this study (Fig. 1a).…”
Section: Stromule Frequency In Light and Dark Conditions In Arabidopssupporting
confidence: 74%
“…We observed stomatal guard cell chloroplasts and counted the frequency of stromules in 1-and 2-day old cotyledons, taken as a developing leaf, and 5-day old cotyledons, as a developed leaf. Abnormal morphology of chloroplasts in stomata has not been reported in wild-type seedlings (Fujiwara et al 2018) and we observed normal morphology of the chloroplasts in stomata and pavement cells in this study (Fig. 1a).…”
Section: Stromule Frequency In Light and Dark Conditions In Arabidopssupporting
confidence: 74%
“…Seeds of plastid division mutants, parc6-1 (SALK_100009; Glynn et al, 2009;Zhang et al, 2009;Ottesen et al, 2010;generated by Alonso et al, 2003), parc6-3 (Glynn et al, 2009), parc6-4 (SALK_138043; Zhang et al, 2009; generated by Alonso et al, 2003), arc6-3 (CS288; , and arc11-1 (CS281; Marrison et al, 1999) were obtained from the Arabidopsis Biological Resource Center (ABRC), Ohio State University, Columbus, OH, USA. Two transgenic Arabidopsis lines [FL4-4 and FL6-4; Columbia (Col) background] expressing organelle-targeted fluorescent proteins as well as offspring derived from crosses between the transgenic lines and mutants (parc6-1 × FL4-4, parc6-3 × FL4-4, parc6-4 × FL4-4, arc11-1 × FL4-4, and arc6-3 × FL6-4) were used (Chen et al, 2009;Itoh et al, 2010;Fujiwara et al, 2018;Itoh et al, 2018; see summary in Table 1). The parc6-5 (suba2) mutant was isolated from EMS-treated FL4-4 seeds carrying two nucleotide substitutions in the PARC6 coding sequence, resulting in G62R and W700stop mutations at the protein level (Itoh et al, 2018).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Basal parts of leaves including petioles were excised from Arabidopsis seedlings using tweezers. Based on previous observations (e.g., Fujiwara et al, 2004;Fujiwara et al, 2008;Fujiwara et al, 2009a;Fujiwara et al, 2009b;Itoh et al, 2010;Fujiwara et al, 2015;Fujiwara et al, 2017;Fujiwara et al, 2018;Itoh et al, 2018), the adaxial surface of the leaf epidermis in the upper petiole region was used to analyze leaf pavement, trichome, and guard cells in Arabidopsis, unless otherwise specified.…”
Section: Fluorescence Stereomicroscopy and Epifluorescence Microscopymentioning
confidence: 99%
See 2 more Smart Citations